Influences of supervisory styles on talent development, turnover intention and mediating role of clinical learning environment among trainee doctors in Malaysia - Subramaniam, Anusuiya (2014)
Examination on the literature indicated that no empirical research has integrated the concepts of supervisory styles (coaching, mentoring, participative and abusive supervision), clinical learning environment, talent development (development of professional and medical competencies) and turnover intention. In addition, there were less talent development studies in testing the mediating role of clinical learning environment. Thus, the main objective of this study is to examine the influences of supervisory styles on talent development, turnover intention and the mediating role of clinical learning environment among trainee doctors in Malaysian public hospitals. A survey questionnaire was administered on trainee doctors undergoing housemanship training at public hospitals in Klang Valley, Malaysia, and the survey yielded 355 responses. They were choosen using a systematic sampling procedure. Trainee doctors’ talent development was conceptualized using the evidence-based management theory. The theory highlights that doctors possess the craft that can be learned or developed through practice and experience with appropriate supervision. The findings indicate the following: high level of talent development and low level of turnover intention; high preference for coaching supervision, moderate preference for mentoring supervision, high preference for participative supervision and low preference for abusive supervision; coaching, mentoring, participative and abusive supervision influences clinical learning environment, coaching and mentoring supervision facilitates talent development, participative supervision and abusive supervision influences turnover intention and clinical learning environment influences talent development. In addition, the findings reveal that clinical learning environment mediates the relationship between supervisory styles (participative and abusive supervision) and talent development. However, contrary to expectation, coaching and mentoring supervision is not linked to turnover intention; there is no direct effect between supervisory styles (participative and abusive supervision) and talent development; and clinical learning environment is not linked to turnover intention, respectively. As a whole, this study has shed some light on the supervisory styles that can facilitate talent development and influence turnover intention, as well as the influence of clinical learning environment among trainee doctors in Malaysian public hospitals. This study can be a stepping stone for other researchers as this is one of the first few empirical studies done on human resource development, talent development and talent retention among medical practitioners.